Efektivitas Pelayanan Perizinan Bidang Penelitian dan Pelatihan melalui ‘SiRinduNona’ (Sistem Perizinan Terpadu Non Berusaha) pada DPMPTSP Kabupaten Jombang - Indera Hayati, Aulia Dian; Noviyanti (Universitas Negeri Surabaya, 2023)
Licensing services through 'SiRinduNona' at the Investment and One-Stop Service Office of Jombang Regency is a form of public service provided by government agencies to the community but in practice there are several problems so that licensing services through 'SiRinduNona' are not fully effective. There are still many licensing users who do not understand licensing through 'SiRinduNona', the long licensing process, the lack of HR skills in the IT field at DPMPTSP. So the purpose of this study is to describe and analyze the effectiveness of Licensing Services in the Field of Research and Training through 'SiRinduNona' at the Investment and One-Stop Services Office. This type of research is descriptive qualitative. Data collection techniques are carried out by observation, interviews, and documentation. The results of the study show that in licensing services in the field of research and training through 'SiRinduNona' it has been running effectively. However, there is one indicator that has not been effective, namely the integration indicator. In the indicator of integration of human resources in terms of quality they do not understand the process of making permits through 'SiRinduNona' this is related to the absence of socialization carried out by DPMPTSP in the field of research and training, DPMPTSP implementers also do not all understand IT related so they still depend on the head of the IT sector . Making permits through 'SiRinduNona' is also not in accordance with the time provisions in the SOP because OPD executors have other work priorities, causing a delay in the time for making the permit process. The advice given to the DPMPTSP of Jombang Regency is that socialization should be held regarding licensing services in the research and training sector as well as other fields, bearing in mind that licensing through 'SiRinduNona' is not only in the health sector. As well as providing evaluations to employees regarding performance in providing fast service in accordance with procedures and an increase in the ability of the IT field in more knowledge to solve problems if a system down occurs. Keywords: Effectiveness, Licensing Services, 'SiRinduNona'.